Characterization of glycolytic initial metabolites and enzyme activities in developing sunflower (Helianthus annuus L.) seeds. - Troncoso-Ponce, M; Kruger, N; Ratcliffe, G; Garcés, R; Martínez-Force, E (2009)
Unlike other oilseeds (e.g. Arabidopsis), developing sunflower seeds do not accumulate a lot of starch and they rely on the sucrose that comes from the mother plant to synthesise lipid precursors. Between 10 and 25 days after flowering (DAF), when sunflower seeds form and complete the main period of storage lipid synthesis, the sucrose content of seeds is relatively constant. By contrast, the glucose and fructose content falls from day 20 after flowering and it is always lower than that of sucrose, with glucose being the minor sugar at the end of the seed formation. By studying the apparent kinetic parameters and the activity of glycolytic enzymes in vitro, it is evident that all the components of the glycolytic pathway are present in the crude seed extract. However, in isolated plastids important enzymatic activities are missing, such as the glyceraldehyde-3-phosphate dehydrogenase, involved in the conversion of glyceraldehyde 3-phosphate into 1,3-biphospho-glycerate, or the enolase that converts 2-phosphoglycerate into phosphoenolpyruvate. Hence, phosphoenolpyruvate or one of its derivatives, like pyruvate and malate from the cytosol, may be the primary carbon sources for lipid biosynthesis. Accordingly, the glucose-6-P imported into the plastid is likely to be used in the pentose phosphate pathway to produce the reducing power for lipid biosynthesis in the form of NADPH. Data from crude seed extracts indicate that enolase activity increased during seed formation, from 16 days after flowering, and that this activity was well correlated with the period of storage lipid synthesis. In addition, while the presence of some glycolytic enzymes increased during lipid synthesis, others decreased, remained constant, or displayed irregular temporal behaviour.